The The Effect of Application Various Doses of Cow Manure and NPK (16:16:16) on Soil Properties and The Growth of Red Lettuce (Lactuca sativa Var. Acephala) - Bq. Windriyani Lestari; I Putu Silawibawa; R. Sutriono (Jurnal Biologi Tropis, 2023)
Red lettuce is one of the horticultural crops that has many benefits and can increase the economic income of farming families. Cultivation of red lettuce plants requires proper maintenance and fertilization to increase the yield of red lettuce plants. To complement nutrients, the addition of organic and NPK fertilizers is required. The purpose of this study is to determine the effect of cow manure and NPK fertilizers 16:16:16 on soil properties and the growth of red lettuce plants (Lactuca sativa Var. Acephala). The method used in this research is an experimental method with a Completely Randomized Design (CRD) experiment consisting of two factors, namely factor I is cow manure (K) and factor II is Pearl NPK fertilizer (16:16:16) (P). Each treatment was repeated 3 times so that a total of 27 experimental polybags were obtained. The treatment with cow manure 10 tons/ha has the best value of C-organic (3.55%) and porosity (56.76%). The highest weight of wet stems of red lettuce plants was obtained in the treatment of 300 kg/ha NPK fertilizer and 10 tons/ha cow manure at 35.14 grams.